A Systematic Literature Review of Healthcare Total Quality Management, Sustainable Hospital Governance, and Sustainable Competitive Advantage - Waluyo Dwi Cahyono; Supardi Supardi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
The healthcare industry faces various challenges due to technological advancements, rising patient expectations, regulatory changes, and increasingly intense competition. These conditions require hospitals to develop strategic capabilities to achieve sustainable competitive advantage. This study aims to identify, evaluate, and synthesize the results of previous research on the relationship between Healthcare Total Quality Management (HTQM), Sustainable Hospital Governance (SHG), and Hospital Sustainable Competitive Advantage (HSCA). The study employs a Systematic Literature Review (SLR) method in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search was conducted in the Scopus, Web of Science, ScienceDirect, Emerald Insight, PubMed, and Google Scholar databases, covering publications from 2015 to 2025. Of the 420 articles identified, 15 met the inclusion criteria and were analyzed using a thematic content analysis approach. The synthesis results indicate that HTQM plays a crucial role in improving service quality, patient safety, operational efficiency, patient satisfaction, and organizational performance through a culture of continuous improvement. Additionally, SHG strengthens organizational sustainability through the application of the principles of transparency, accountability, responsibility, and stakeholder engagement. From the perspective of the Resource-Based View (RBV), HTQM and SHG are strategic capabilities that are valuable, rare, difficult to imitate, and not easily replaceable, thereby creating sustainable competitive advantage. This study also produced a conceptual framework that integrates HTQM and SHG as the foundation for building sustainable competitive advantage in hospitals. The research findings provide a theoretical contribution to the development of the literature on strategic hospital management, as well as practical implications for hospital administrators in formulating strategies for quality improvement and governance oriented toward sustainability.